Pengaruh Kondisi Keuangan Pemerintah dan Kualitas Demokrasi terhadap Kesejahteraan Wilayah di Indonesia Tahun 2022 dengan Pendekatan Structural Equation Modeling-Partial Least Square (SEM PLS) - Mandiri, Angga Jati; Sirait, Timbang (Politeknik Statistika STIS, 2024)
Indonesia, adopting concept of welfare state, still has welfare issues, making Indonesia's regional welfare worse than several Southeast Asian countries. Indicates that Indonesia's regional welfare still needs to be improved. The approach is not only through socio-economic aspects, but also through political aspects. This study offers a political approach to financial sector with government financial conditions and mediating role of non-financial sector with quality of democracy. This study purposes to determine direct and indirect effects of government financial conditions and quality of democracy on regional welfare in Indonesia 2022. The analysis uses Structural Equation Modeling-Partial Least Square (SEM-PLS) approach with 34 provinces in Indonesia as unit analysis. The results show that both have direct positive significant effect on regional welfare. Government financial condition has a direct positive significant effect on quality of democracy. Also, quality of democracy significantly mediates the effect of government financial conditions on regional welfare in Indonesia.